Penerapan Secure Coding Sebagai Cyber Security Based Pada PT. Industri Karet Deli - Denny Ramahdana; Zuhri Ramadhan (CV. Hawari, 2025)
Cyber security is a crucial aspect in maintaining the integrity, confidentiality, and availability of a company's information systems. PT. Industri Karet Deli, as one of the national manufacturing companies that has implemented digital systems in its operations, faces significant challenges in terms of potential cyber threats. This study aims to apply secure coding principles as the basis for strengthening cyber security systems. The methods used include identifying security vulnerabilities in the company's internal applications, evaluating the source code, and implementing secure coding practices in accordance with OWASP (Open Web Application Security Project) standards. The research results show that the systematic implementation of secure coding can reduce system vulnerabilities by up to 60% compared to before implementation. These findings emphasize the importance of integrating security from the early stages of software development to create systems that are resilient to cyber attacks. Recommendations from this study include regular training for development teams and the adoption of code review policies as part of the continuous system development process.